Estudo eletroquímico da minociclina e sua determinação em leite materno e em formulação farmacêutica por voltametria de pulso diferencial - Souza, Michel Rafael dos Santos (2012)
In this work was developed an electroanalytical methodology for determination of the antibiotic minocycline in pharmaceutical formulation and in human milk using differential pulse voltammetry. The voltammograms of the minocycline obtained with carbon paste electrodes showed a well-defined peak at 0.40 V vs. Ag/AgCl, corresponding to the oxidation of minocycline at pH 4.0. The electrodic behavior involved a reversible oxidation process and mass transport controlled by diffusion. The value of the effective area calculated for the carbon paste electrode was 0.3313 cm2, corresponding to a geometric area of 0.0078 cm2. After the optimization of the experimental conditions, such as, pH 4.00; scan speed 30 mV s-1, amplitude 100 mV; analytical curves were obtained in the linear concentration range from 2.0 to 23 μmol L-1 resulting in a detection limit of 0.7 μmol L-1 and the quantification limit of 2.2 μmol L-1. In order to evaluate the robustness of the proposed method the presence of possible interfering was analyzed in the determination of the minocycline, it was observed the interference of the folic acid, ketoconazole and dipyridamole among the possible evaluated interfering. To check the applicability of the developed method were analyzed previously in the optimized conditions, commercial samples of pharmaceutical formulations, one liquid and another in tablet, obtaining a recovery of 100 and 99.3%, respectively; and samples of maternal milk, obtaining a recovery of 96%. In addition to advantages such as high selectivity and sensitivity, the method developed could be used for the analysis of minocycline in pharmaceutical formulation and human milk without any need for prior sample treatment.